Observations of cosmic ray variations by the CARPET detector during the period from 4 to 10 September, 2017 - Морзабаев, М. Қ.; Шагдар , Н. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
Data on the radiation parameters of proton events and the intensity of galactic cosmic rays are of practical interest for estimating the radiation situation in near-Earth space. Therefore, this article presents brief characteristics of the CARPET cosmic ray detector for continuous observation of the cosmic ray flux at the Earth level and the results of analysis of variations in the intensity of cosmic rays recorded during the solar proton event from September 4 to September 10, 2017. Also, data on the observed Forbush decrease during this period are provided.